Analisis Ancaman Terhadap Keamanan Data Pribadi pada Email - Wahyu Hidayat M; Nurhayi Musdira; Natatsa Rasyid; Miftahul Khairi S; Muh Juharman (Sakura Digital Nusantara, 2023)
Today's technological advances cannot be separated from people's lives. Basically, technology was created to facilitate human work. One of the very rapid technological developments is in the field of communication technology. The communication technology that is widely used in the world is email. Email is a very popular application and is used every day for personal, business or for official because it has many positive things. But on the other hand, email also has a negative impact. Due to the large use of email, many criminals use email to steal user privacy or other nefarious purposes. The research method used is quantitative research method. Data collection was carried out by collecting data from student surveys of the Department of Informatics and Computer Engineering, Makassar State University. This study was conducted by distributing research questionnaires. Therefore, we need to analyze what are the threats to email in order to avoid theft of personal data and other threats.